A Study on the Influence of Promotion of Garuda Indonesia by Social Media on e–WOM, Online Ticket Sales, Brand Image, and Brand Loyalty During the Covid-19 Pandemic (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study investigates the impact brand identity of three of the promotional information characteristics of airline social media information quantity, credibility of information, and quality of information through electronic word-of - mouth (e-WOM). We did a survey 250 customers who had been using social media from Garuda Indonesia airlines to interpret and evaluate data obtained using structural equations. The findings of this study showed that the promotion of social media airlines had a positive impact on e-WOM, e-WOM had such a positive effect on the brand's image and e-WOM even had a noticeable impact on the selling of online tickets. This study sets out a model for social media information characteristics and can be used as basic data to illustrate how airlines can handle and use social media information.